Comparative Study Of Salt Brand Rapid Consumption In The Flotation Process Of Intestinal Nematode Eggs - Rony Puasa; Jusuf Kristianto (Jurnal Health Sains, 2024)
Introduction: Based on its type, salt consists of; industrial salt, curing salt, table salt, and consumption salt. Consumable salt can be used as an alternative material in the flotation method. It has been proven in previous research (2021) that salt consumption can cause intestinal nematode eggs to float. The concentration used in the research was 32%. The aim is to find out the fastest time for the brand of salt consumed in the intestinal nematode egg flotation process. Method: This research is an experimental laboratory research, using samples of consumption salt with a concentration of 32%, adding a suspension of intestinal nematode worm eggs, then observing the flotation. Results; There is no time difference between JPL and BTM brands of salt because consuming both types of salt from the first 10 minutes of the experiment can cause flotation until the last minute of the experiment, namely the 40th minute, still causes flotation. Conclusion ; The results of the experiment guarantee that the two types (brands) of salt consumed are; JPL and BTM with a concentration of 32% can both cause intestinal nematode eggs to float, starting from the first 10 minutes to 40 minutes